2010
DOI: 10.1016/j.polymer.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation during tensile drawing of annealed high density polyethylene

Abstract: The annealing of semicrystalline polymers usually leads to the crystal refinement and thickening. It appears that also the cavitation during tensile drawing is affected. In the uniaxially drawn high density polyethylene a massive cavitation was detected by X-ray scattering in samples previously annealed at 125 o C. The number of voids depends on the annealing time, while their size and orientation depends on the local strain. The cavitation resulted in 30% increase of volume for annealed samples, strained to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 42 publications
7
53
0
Order By: Relevance
“…Otherwise, fragmentation of crystal lamellae is preferred. This outcome is compatible with the independent observations of Pawlak and Galeski [15]. In their former work [11], it was found that cavities are formed readily in HDPE, i-PP, and POM while they do not occur in lowdensity polyethylene (LDPE), PA6, and ethylene-octene copolymer.…”
Section: Nanocavitationsupporting
confidence: 89%
See 1 more Smart Citation
“…Otherwise, fragmentation of crystal lamellae is preferred. This outcome is compatible with the independent observations of Pawlak and Galeski [15]. In their former work [11], it was found that cavities are formed readily in HDPE, i-PP, and POM while they do not occur in lowdensity polyethylene (LDPE), PA6, and ethylene-octene copolymer.…”
Section: Nanocavitationsupporting
confidence: 89%
“…Along with the well-established data, new findings regarding structural defects occurring at small strains as well as their role in the global deformation behavior of semicrystalline polymers will be highlighted. At low strain level, stretching favors the occurrence of different structural defects such as nanocavities in the interlamellar amorphous layers [8][9][10][11][12][13][14][15][16][17][18][19] and damages of crystalline lamellae [20][21][22]. These imperfections could lead either to softening or modification of the plastic deformation mechanisms of semicrystalline polymers.…”
Section: Introductionmentioning
confidence: 99%
“…14. In the case of PP-N ( Fig. 14 (a)), the SAXS profiles showed a monotonic-like decrease without a distinct peak at each layer, which is usually observed in the void formation in semi-crystalline polymers [29,30,49]. This result indicates that inhomogeneous voids with a broad size distribution were formed in PP-N.…”
Section: Scanning Microbeam Small Angle X-ray Scatteringmentioning
confidence: 70%
“…Annealing also changes the cavitation behavior, which is closely related to the deformation mechanism [27e29]. For example, Pawlak and Galeski investigated the effect of annealing on the cavitation behavior of various high-density polyethylene samples with a spherulite structure [30]. They reported that the annealing induced a massive cavitation, giving rise to a decrease in the localization of the plastic deformation after the yielding.…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation behavior has been found in many semi-crystalline polymers, including isotacticpolypropylene (iPP) [1,2], polyethylene (PE) [3,4], poly(1-butene) (P1B) [5], and so on, when these polymers are stretched above their glass transition temperature. Stress whitening can be regarded as the scattering of visible light by voids detected by naked eye.…”
Section: Cavitation Behavior Of Semi-crystalline Polymersmentioning
confidence: 99%